1998
DOI: 10.1111/1469-8986.3520199
|View full text |Cite
|
Sign up to set email alerts
|

Emotional arousal and activation of the visual cortex: An fMRI analysis

Abstract: Functional activity in the visual cortex was assessed using functional magnetic resonance imaging technology while participants viewed a series of pleasant, neutral, or unpleasant pictures. Coronal images at four different locations in the occipital cortex were acquired during each of eight 12-s picture presentation periods (on) and 12-s interpicture interval (off). The extent of functional activation was larger in the right than the left hemisphere and larger in the occipital than in the occipitoparietal regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

33
219
0
2

Year Published

2000
2000
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 632 publications
(254 citation statements)
references
References 12 publications
33
219
0
2
Order By: Relevance
“…For instance, the need for additional time to initially identify negative images might explain why negative images tend to hold attention longer than positive images (Amir et al, 2003;Fox, Russo, & Dutton, 2002;Koster et al, 2004). In addition, the finding that negative images require more time to identify may suggest that the increased cortical activity for negative stimuli found with fMRI (Lang et al, 1998;LeDoux, 2000;Phelps & LeDoux, 2005;Sergerie, Chochol, & Armony, 2008;Vuilleumier, 2005) and ERP (Olofsson, Nordin, Sequeira, & Polich, 2008) reflects the increased time and effort required to complete identification rather than a more extensive processing of those stimuli. …”
Section: Discussionmentioning
confidence: 99%
“…For instance, the need for additional time to initially identify negative images might explain why negative images tend to hold attention longer than positive images (Amir et al, 2003;Fox, Russo, & Dutton, 2002;Koster et al, 2004). In addition, the finding that negative images require more time to identify may suggest that the increased cortical activity for negative stimuli found with fMRI (Lang et al, 1998;LeDoux, 2000;Phelps & LeDoux, 2005;Sergerie, Chochol, & Armony, 2008;Vuilleumier, 2005) and ERP (Olofsson, Nordin, Sequeira, & Polich, 2008) reflects the increased time and effort required to complete identification rather than a more extensive processing of those stimuli. …”
Section: Discussionmentioning
confidence: 99%
“…It is therefore possible that like the findings of Holmes, et al (2008), high-anxious individuals in the current study showed an enhanced P1 and a reduced N1, a pattern similar to the P1 and EPN findings in the Holmes, et al study. The enhanced P1 seen in high-anxious individuals may be taken as a sign of increased sensory processing of the faces, most likely due to projections from the amygdala or other motivational centers to the visual cortex (Lang, Bradley, et al, 1998;Pourtois, Grandjean, Sander, and Vuilleumier, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Theoretically, the sensitivity can be improved by longer task durations and by individually tuning the set of presented pictures, based on individual subject emotional responses before imaging sessions (Lang, et al 1998). In the later case, subjects would have to be scanned after a sufficiently long period of time to preserve novelty and to produce a high emotional response.…”
Section: Discussionmentioning
confidence: 99%